Misunderstandings in Student Communication in Various Universities - Rani Siti Fitriani; Siti Salina; Nazwa Maharani; Albertha Sonia Br.Tamba; Revi Yuniar Hajar (Universitas Serambi Mekkah, 2024)
Communication is a human need to interact with others in various daily activities. A person will convey ideas, opinions, thoughts, feelings to others by communicating using language in writing and speech. We cannot deny that in communicating, misunderstandings often occur between speakers and speech partners or writers and readers. The impact of misunderstanding is a relationship that is no longer harmonious or good such as feuds, quarrels, and hostility. This study aims to analyze the phenomenon of misunderstanding in communication in a teenage environment. This research uses a qualitative research method with a descriptive approach to understand complex phenomena. The researcher collected data through 20 respondents, observation, and document analysis to identify how ambiguity arises in communication and its impact on interactions between individuals. The results showed that the majority of respondents experienced miscommunication through text media which often led to misunderstandings compared to direct or face-to-face communication.